Testing for subsphericity when n and p are of different asymptotic order - Virta Joni (Elsevier B.V., 2025)
We extend a test of subsphericity to the high-dimensional Gaussian regime where the spikes diverge to infinity and p/n → {0, ∞}. The test is used to derive a consistent estimator for the latent dimension of the model.